The Application of Community Accounting for Strengthening the Management of Bantengan Art Preservation - Ana Sopanah; Kusila Meyrin Rossalia; Indana Jamila Novianti; Midhatul Khasanah; Mohammad Supriyadi (Journal of Society, Community and Business Development, 2025)
This community service program focuses on the challenges faced by the Bantengan art community in Greater Malang, particularly the weak financial management and organizational accountability. This topic was chosen because transparency is considered essential for maintaining the sustainability of traditional arts and enhancing public trust. The method employed was a Community-Based Research (CBR) approach, involving observation, in-depth interviews, focus group discussions, training, and participatory mentoring with community leaders. The main outcomes of this activity include the preparation of a simple cash book, the first monthly financial report, financial SOPs, and organizational restructuring, with an additional achievement of a 20% increase in turnover. These findings demonstrate that community-based accounting practices not only improve financial administration but also strengthen social legitimacy and institutional sustainability. Thus, this program highlights the importance of a simple accounting system rooted in local wisdom to support the preservation and development of traditional arts.